Institutionalization of the 5E Instructional Model Integrated Augmented Reality Interactive Book (5E-IMARIB): Its Impact in Increasing Students' Understanding of 3D Geometry Concepts and Self-Efficacy? - Sudirman, Sudirman; Dejarlo, Jenisus; Susandi, Ardi Dwi; Triyono, Didik (Jurnal Pendidikan MIPA, 2024)
3D geometry is an abstract concept that provides a visual representation of shape and space in mathematics. However, many students consider images in books to be representations of 3D geometry, thus requiring direct visualization for better understanding. Therefore, this research aims to institutionalize the use of 5E-IMARIB in 3D geometry learning to influence students' understanding of 3D geometry concepts and increase students' self-efficacy in geometry subjects. A quasi-experimental nonequivalent comparison group design was used in this research. Participants in this research were class VIII students at one of the private junior high schools in Indramayu Regency, who were then selected into two classes. The first class consisted of 20 students learning using the 5E-IMARIB, and in the second class, 22 students were using conventional learning. Data obtained from the results of the geometry understanding test and self-efficacy questionnaire were analyzed quantitatively using the independent t-test. The results showed that the average pre-test score for the experimental class was 17.83 and the average post-test score was 63.43. The average score of student learning outcomes in the control class was 18.78 for the pre-test and 52.35 for the post-test. Meanwhile, the average gain score in the experimental class was 0.52, and in the control class 0.41. Apart from that, the average increase in self-efficacy (SE) in the experimental class was 0.22, and in the respondent class was 0.20. Furthermore, based on statistical analysis using an independent t-test, it was concluded that there was an increase in understanding of 3D geometry concepts and students' self-efficacy after using 5E-IMARIB . The results of this research indicate that AR in 3D geometry learning has the potential to help students understand geometric concepts and student affectivity.         Keywords: 5E instructional model, augmented reality interactive book, 3D geometry, understanding of  geometry concepts, self-efficacy.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp195-209